THE INFLUENCE OF TRAINING AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT SAMWON COPPER TUBE INDONESIA - Prasetyo Kurniawan (International Journal Multidisciplinary Science, 2024)
The objective of this study is to determine the influence of training and work environment on employee performance at PT Samwon Copper Tube Indonesia in Tangerang Regency, Banten. The method used is quantitative. The sampling technique used is saturated sampling, meaning all members of the population are used as the sample, resulting in a sample of respondents in this study. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The study results indicate that training has a positive and significant effect on employee performance, with a regression equation showing a direct relationship. The coefficient of determination shows that part of the variation in employee performance can be explained by the training variable, and hypothesis testing results indicate a positive and significant influence of training on employee performance at PT Samwon Copper Tube Indonesia in Tangerang Regency, Banten. The work environment also has a positive and significant effect on employee performance, with a regression equation showing a direct relationship. The coefficient of determination shows that part of the variation in employee performance can be explained by the work environment variable, and hypothesis testing results indicate a positive and significant influence of the work environment on employee performance at PT Samwon Copper Tube Indonesia in Tangerang Regency, Banten. Training and work environment simultaneously have a positive and significant effect on employee performance, with a regression equation indicating the contribution of these two variables together. The coefficient of determination shows that a large portion of the variation in employee performance can be explained by training and work environment, while the remainder is influenced by other factors. Hypothesis testing results indicate a positive and significant influence of training and work environment simultaneously on employee performance at PT Samwon Copper Tube Indonesia in Tangerang Regency, Banten.